Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Given the equation [tex]\(|3x - 9| - 24 = -12\)[/tex], let's simplify it to understand which relationships are equivalent.
Step-by-Step Simplification:
1. Starting Equation:
[tex]\[ |3x - 9| - 24 = -12 \][/tex]
2. Isolate the Absolute Value Expression:
Add 24 to both sides:
[tex]\[ |3x - 9| - 24 + 24 = -12 + 24 \][/tex]
[tex]\[ |3x - 9| = 12 \][/tex]
So, the equation simplifies to:
[tex]\[ |3x - 9| = 12 \][/tex]
3. Solving the Absolute Value Equation:
The absolute value equation [tex]\(|A| = B\)[/tex] has two solutions:
[tex]\[ A = B \quad \text{or} \quad A = -B \][/tex]
For our equation [tex]\(|3x - 9| = 12\)[/tex], the solutions are:
[tex]\[ 3x - 9 = 12 \quad \text{or} \quad 3x - 9 = -12 \][/tex]
4. Solve for [tex]\(x\)[/tex] in Both Cases:
- Case 1: [tex]\(3x - 9 = 12\)[/tex]
[tex]\[ 3x = 12 + 9 \][/tex]
[tex]\[ 3x = 21 \][/tex]
[tex]\[ x = 7 \][/tex]
- Case 2: [tex]\(3x - 9 = -12\)[/tex]
[tex]\[ 3x = -12 + 9 \][/tex]
[tex]\[ 3x = -3 \][/tex]
[tex]\[ x = -1 \][/tex]
So, the solutions to the simplified equation are [tex]\(x = 7\)[/tex] and [tex]\(x = -1\)[/tex].
Based on this, we can determine which relationships are equivalent to [tex]\(|3x - 9| - 24 = -12\)[/tex]:
1. [tex]\(3x - 9 = -36\)[/tex] or [tex]\(3x - 9 = 36\)[/tex]
- These equations are not equivalent to [tex]\(|3x - 9| = 12\)[/tex].
2. [tex]\(x = -9\)[/tex] or [tex]\(x = 15\)[/tex]
- These solutions do not match our simplified equation [tex]\(|3x - 9| = 12\)[/tex].
3. [tex]\(3x - 9 = -12\)[/tex] or [tex]\(3x - 9 = 12\)[/tex]
- These are equivalent to the simplified equation [tex]\(|3x - 9| = 12\)[/tex].
4. [tex]\(x = -1\)[/tex] or [tex]\(x = 7\)[/tex]
- These are the solutions to our simplified equation, so they are equivalent.
5. [tex]\(|3x - 9| = 12\)[/tex]
- This is the simplified form of our original equation, so it is obviously equivalent.
6. [tex]\(|3x - 9| = 36\)[/tex]
- This equation is not equivalent to the simplified form [tex]\(|3x - 9| = 12\)[/tex].
Thus, the correct answers are:
- [tex]\(3 x-9=-12\)[/tex] or [tex]\(3 x-9=12\)[/tex]
- [tex]\(x=-1\)[/tex] or [tex]\(x=7\)[/tex]
- [tex]\(|3 x-9|=12\)[/tex]
Step-by-Step Simplification:
1. Starting Equation:
[tex]\[ |3x - 9| - 24 = -12 \][/tex]
2. Isolate the Absolute Value Expression:
Add 24 to both sides:
[tex]\[ |3x - 9| - 24 + 24 = -12 + 24 \][/tex]
[tex]\[ |3x - 9| = 12 \][/tex]
So, the equation simplifies to:
[tex]\[ |3x - 9| = 12 \][/tex]
3. Solving the Absolute Value Equation:
The absolute value equation [tex]\(|A| = B\)[/tex] has two solutions:
[tex]\[ A = B \quad \text{or} \quad A = -B \][/tex]
For our equation [tex]\(|3x - 9| = 12\)[/tex], the solutions are:
[tex]\[ 3x - 9 = 12 \quad \text{or} \quad 3x - 9 = -12 \][/tex]
4. Solve for [tex]\(x\)[/tex] in Both Cases:
- Case 1: [tex]\(3x - 9 = 12\)[/tex]
[tex]\[ 3x = 12 + 9 \][/tex]
[tex]\[ 3x = 21 \][/tex]
[tex]\[ x = 7 \][/tex]
- Case 2: [tex]\(3x - 9 = -12\)[/tex]
[tex]\[ 3x = -12 + 9 \][/tex]
[tex]\[ 3x = -3 \][/tex]
[tex]\[ x = -1 \][/tex]
So, the solutions to the simplified equation are [tex]\(x = 7\)[/tex] and [tex]\(x = -1\)[/tex].
Based on this, we can determine which relationships are equivalent to [tex]\(|3x - 9| - 24 = -12\)[/tex]:
1. [tex]\(3x - 9 = -36\)[/tex] or [tex]\(3x - 9 = 36\)[/tex]
- These equations are not equivalent to [tex]\(|3x - 9| = 12\)[/tex].
2. [tex]\(x = -9\)[/tex] or [tex]\(x = 15\)[/tex]
- These solutions do not match our simplified equation [tex]\(|3x - 9| = 12\)[/tex].
3. [tex]\(3x - 9 = -12\)[/tex] or [tex]\(3x - 9 = 12\)[/tex]
- These are equivalent to the simplified equation [tex]\(|3x - 9| = 12\)[/tex].
4. [tex]\(x = -1\)[/tex] or [tex]\(x = 7\)[/tex]
- These are the solutions to our simplified equation, so they are equivalent.
5. [tex]\(|3x - 9| = 12\)[/tex]
- This is the simplified form of our original equation, so it is obviously equivalent.
6. [tex]\(|3x - 9| = 36\)[/tex]
- This equation is not equivalent to the simplified form [tex]\(|3x - 9| = 12\)[/tex].
Thus, the correct answers are:
- [tex]\(3 x-9=-12\)[/tex] or [tex]\(3 x-9=12\)[/tex]
- [tex]\(x=-1\)[/tex] or [tex]\(x=7\)[/tex]
- [tex]\(|3 x-9|=12\)[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.